UNITED WE STAND - DIVIDED WE FALL: ASSESSING THE POTENTIAL OF THE EU AND ITS CITIZENS TO CONFRONT THE CORONAVIRUS PANDEMIC AS A CHANCE TO REAFFIRM THE EUROPEAN IDENTITY (EU and comparative law issues and challenges series (ECLIC), 2021)
The main aim of this paper is to assess the potential of the EU and its citizens to face the Coronavirus pandemic as a chance to reaffirm the European identity. This paper consists of three complementary parts. In the first part conceptualization of the European identity is presented according to the views of the EU institutions and relevant authors with purpose to signify its importance for further development of the EU project. In the second part the extent to which the EU citizens are currently affiliated with the European Union is assessed, especially with regard to the response of the EU to confront the pandemic (i.e. by relying on recent Eurobarometer surveys). Third and the central part of this paper is focused on providing the review and analysis of relevant solidarity actions directed to confront Coronavirus crisis by the EU institutions and representative CSOs active specifically at the EU level in the field of promoting European citizenship. The key findings of this inquiry indicate that analysed initiatives contain solidarity dimension, and therefore, have potential to reaffirm the European identity, that is, to enhance cohesion and unity among the EU citizens.